Analisis Tingkat Kepuasan Masyarakat terhadap Kinerja Pemerintahan Distrik Soyoi Mambai (Sombai) Kabupaten Waropen - John Frits Ayomi (Global Leadership Organizational Research in Management, 2025)
This study aims to determine what indicators are generally considered by the public in assessing the performance of the Government in Soyoi Mambai District (Sombai) Waropen Regency, and how much importance is given to each factor?; 2) How big is the gap between public expectations and the actual conditions of Government performance and 3) What is the level of public satisfaction with the performance of the Soyoi Mambai District Government (Sombai) Waropen Regency? The study was conducted in Soyoi Mambai District, Waropen Regency. The type of research used is descriptive with qualitative and quantitative approaches. The research instrument used is a questionnaire. The population in this study is all adults in Soyoi Mambai District. The research sample amounted to 200 respondents. Data collection uses primary and secondary data. Data analysis uses the Multiindicator Attitude Model (MAM). The results of the study indicate that: 1) The indicators used to assess the performance of Soyoi Mambai District Government Officials, Waropen Regency are Responsibility (Indicator I1), Public Oriented (I2), Democratization (I3), Bureaucracy System (I4), Natural Resources Management (I5) and Transparency Financing (I6), 2) A gap of 4.22 in the Public Oriented indicator (Indicator I2) indicates the low commitment of Soyoi District Government Officials in prioritizing public interests over personal interests and other types of interests and 3) The Soyoi Mambai community feels "Somewhat Satisfied" with the Performance of Soyoi Mambai District Government Officials.